Opening the Door to Philosophical Inquiry: Reading A Short History of Western Philosophy - TIAN, Ye (Journal of Research for Christianity in China (JRCC), 2024)
Zhao Dunhua, A Concise History of Western Philosophy. Beijing: Peking University Press, 2000. 387,000 characters. Price: ¥23.50.